Pengaruh Citra Merek dan Diferensiasi Produk Shampo Sunsilk Hijab di Kota Praya - Andini, Dwi Tesna (Lembaga Yasin AlSys, 2022)
Sunsilk Hijab Shampoo is one of the pioneers of shampoo for hijab which produced by PT Unilever Indonesia Tbk. Sunsilk Shampoo has been in Indonesia for more than 63 years. However, the increasing number of competitors in this era of globalization, Sunsilk products are increasingly being pushed by existing competitors such as Panten, and Clear and Clean Shampoo. In 2018-2019, Sunsilk released the Sunsilk Hijab variant, with Carla Rizki and Laudya Chintya Bella as a brand ambassador. Sunsilk also uses non-celebrity as brand ambassador for the Sunsilk Hijab Fresh. The purpose of this study is to determine and analyze: (1) the effect of product brand image on purchasing decisions, (2) the effect of differentiation product on purchasing decisions, (3) the effect of brand image and product differentiation and brand image on purchasing decisions. This study uses quantitative research methods, the population in this study are consumers of Sunsilk Hijab Fresh shampoo in Praya, while the sample in this study was 120 respondents. The data collection method in this study used a questionnaire, while the data processing and analysis technique used multiple linear regression analysis. The results of this study indicate that (1) product brand image has a significant influence on purchasing decisions, (2) differentiation product has a significant influence on purchasing decisions, (3) brand image and product differentiation have a simultaneous effect on purchasing decisions. Where product differentiation and brand image have a positive influence on purchasing decisions.